A Multi-Institutional Evaluation of Billing for Tobacco-Cessation Services: Opportunities to Improve Quality and Enhance Revenue Capture - Edward Anselm, MD; Derek J. Baughman, MD; Marcus Rauhut, MS; Taylor Martin, DO, MPH; Ishan Mahajan; Allison B. McCoy, PhD (AJPM Focus)
A recent paper identified significant gaps in billing for tobacco-cessation services for a multihospital health system. Underbilling can reflect poor billing practices, low rates of tobacco-cessation counseling, or a combination of both. The study design was applied to 2 academic medical centers. Deidentified data from the electronic medical records systems were used to identify adult tobacco users and their insurance coverage for patients who had visits to primary care clinics. The proportion of office visits where cessation services were billed was calculated. An economic evaluation of the missed counseling opportunities was based on insurance type and a fee-for-service-payment model. Billing of cessation services is consistently below 2% across the medical centers studied, suggesting substantial opportunities to improve quality and increase revenue. The prevalence of tobacco use in the patient populations studied was significantly lower than reported for that state by the Centers for Disease Control and Prevention.